Software watermarking scheme with cloud computing constraints - Guang SUN; Xiao-ping FAN; Wang-dong JIANG; Hang-jun ZHOU; Sheng-zong LIU; Chun-hong GONG; Jing ZHU (网络与信息安全学报)
A non-equivalent semantic obfuscation-based software watermarking,scheme was introduced to satisfy the demands of software intellectual property breaches in cloud.Via obfuscated source codes,part of semantics was cut into a recovery module to make the source code unavailable.Watermarks map to transform rules were embedded concurrently into these obfuscated codes.The recovery module was a recognizer to prove the watermarks when the original program was recovering.Experimental results,using Java decompliers,indicate that the code become ob-fuscated,is difficult to reverse engineering,thereby mabe the watermarks robust.